Pengembangan Media Pembelajaran E-Modul Fisika Dengan Menggunakan 3D Pageflip Pro Untuk Pokok Bahasan Termodinamika - Mia Aprilia; Reza Tri Gemilang; Rifka Nisa'ul Wahidah (UNIVERSITAS INDRAPRASTA PGRI, 2022)
The research aims to develop e-modules on thermodynamic materials and know students' perceptions. This research is research and development that uses a research and development model. This research procedure adapts the ADDIE development model, which is a development model consisting of five stages consisting of analysis (analysis), design (design), development (development), implementation (implementation), and evaluating (evaluation). The subject of this research trial is a student of class XI IPA 1 sma N 19 kab. Tangerang. The instrument used is a validation questionnaire of media and materials. The data is analyzed descriptively. E-modules developed independently from module covers, concept maps, learning activities per sub-chapter with examples and practice questions and final formative tests. The validation results of media experts are 70%, material experts are 85%, and language experts are 75%, respectively with good categories.